1995
DOI: 10.1177/00494755950250s120
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer in Zaria, Nigeria

Abstract: Skin cancer from 775 patients in the savannah showed a preponderance of squamous cell carcinoma (SCC) of the leg related to neglected, poorly managed and chronic ulcers or scars from burns or injuries. SCC of the head and neck had no predisposing factor. Malignant melanoma overwhelmingly affected the feet, dermatofibrosarcoma affected the trunk and Kaposi sarcoma affected the limbs. Basal cell carcinoma (BCC) comprised only 2% of all skin cancers. The 18 albino patients had a higher frequency of both SCC and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 8 publications
7
33
1
3
Order By: Relevance
“…In our study, head and neck regions were the most common site of malignant tumor and similar findings were noted in other study and also predicted the sun exposure could be the [4][5][6] major e ological factor. One of our case of SCC was in a scar ssue in the right knee, pa ent had history of road traffic accident 12 years back (Figure 2a and 2b).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, head and neck regions were the most common site of malignant tumor and similar findings were noted in other study and also predicted the sun exposure could be the [4][5][6] major e ological factor. One of our case of SCC was in a scar ssue in the right knee, pa ent had history of road traffic accident 12 years back (Figure 2a and 2b).…”
Section: Discussionsupporting
confidence: 90%
“…Plantar melanomas are quite common in sub-Saharan Africa but much less common among African-Americans (Koh, 1991;Ochicha et al, 2004). Previous studies from Tanzania reported Kaposi's sarcoma as the second commonest dermatological malignancy (Amir et al, 1992) whereas Nigerian studies revealed melanomas as more common in Nigeria (Yakubu & Mabogunje, 1995;Adayi & Banjo, 1996;Mandong et al, 2000;Nggada et al, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…Various reports from the literature show wide variations in the prevalence and histological types of dermatological malignancies (Urbach, 1991;Amir et al, 1992, Yakubu & Mabogunje, 1995Adayi & Banjo, 1996;Mandong et al, 2000;Mann & Russel, 2002;Ochicha et al, 2004). While Basal cell carcinoma is undisputedly the commonest dermatological malignancy among Caucasians in Europe, North America and Australia (Urbach, 1991;Mann & Russel, 2002), several studies in Africa reveal a preponderance of squamous cell carcinoma (Amir et al, 1992;Yakubu & Mabogunje, 1995;Adayi & Banjo, 1996;Mandong et al, 2000;Diepgen & Mahler, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations